FUNGI MIKORIZA ARBUSKULA ASAL PANGALENGAN JAWA BARAT SEBAGAI AGENS HAYATI PENGENDALI NEMATODA SISTA KENTANG - Nurbaity, Anne; Sunarto, Toto; Hindersah, Reginawanti; Solihin, Amir; Kalay, Marthin (JURNAL AGROTROPIKA, 2020)
Potato cyst nematode (PCN) is known as organism that could suppress the growth of potatoes and it has been found in West Java. Controlling of PCN by the use of chemical agents has been reduced, hence the use of biological agents such as soil fungi is one of the alternatives. Arbuscular mycorrhizal fungi (AMF) has a potential to be used as a controlling agents. However, the information about it’s effect on nematode, especially in Indonesia is limited. The objectives of this study were to isolate the indigenous AMF from potatoes plantation in a high land at Pangalengan district, West Java, to be used as an agents for controlling nematodes. AMF isolates were cultured and propagated to be used in the test of AMF effectiveness in controlling PCN in a glasshouse. Results showed that AMF at the rate of 150 spores/pot reduced the PCN parameters in term of numbers of juveniles II, fe-males and cysts. The mechanisms of AMF in reducing PCN activities was more likely because of the pro-duction of antifungi isoflavonoid that increased as increasing the rate of AMF spores. The experiment in general showed the successful results in explaining the potential use of AMF as bio-control agents of PCN. Keywords: Arbuscular Mycorrhizal Fungi, Potato Cyst Nematode